PELAKSANAAN PRINSIP TANGGUNG JAWAB SOSIAL PERUSAHAAN TERHADAP LINGKUNGAN(studi pada PT agro Wira ligatsa di kecamatan gunung tuleh kabupaten Pasaman barat) - Inanda U; Fatahillah F; Ramziati R (JURNAL ILMIAH MAHASISWA FAKULTAS HUKUM UNIVERSITAS MALIKUSSALEH, 2023)
Article 74 paragraph (1) of Law Number 40 of 2007 concerning Limited Liability Companies states that companies that carry out their business activities in the fields and / or related to natural resources are obliged to carry out CSR. The purpose of this study is to analyze the implementation of social responsibility at PT Agro Wira Ligatsa towards the environment around the company, obstacles in implementing CSR at PT Agro Wira Ligatsa to the environment around the company and efforts to overcome obstacles in the implementation of social responsibility towards the environment. at PT Agro Wira Ligatsa. This research uses an empirical juridical approach and is descriptive analysis. The sources of legal materials used are primary and secondary legal materials. The technique of collecting legal materials used by researchers is Library Research, which is carried out through searching library materials. Data analysis was carried out by means of descriptive analysis. The results showed that the implementation of Corporate Social Responsibility (CSR) at PT. Agro Wira Ligatsa has not carried out its obligations and is responsible in terms of providing CSR and the safety and comfort of the local community. Programs that have been carried out by the company provide social assistance in the form of food / groceries, qurbani meat every Eid al-Adha, school clothes for local children, and home industry training for mothers who do not have a job. Environmental fields such as tree planting, and education and health sectors such as scholarships. On the other hand, the company has not carried out its obligations in accordance with the laws and licensing requirements in the environmental sector, such as liquid waste that goes directly to residents' plantations, does not have a permit and finds that the flow meter has not been installed at the outlet of the Wastewater Management Institute (IPAL). It is suggested to the Pasaman Regency Government to be more assertive in imposing sanctions on PT Agro Wira Ligatsa if it repeats the same mistake. It is recommended to PT Agro Wira Ligatsa to protect the environment, especially the surrounding community, not only to take advantage of it but also to protect the environment well.